Sleep Deprivation Alters Valuation Signals in the Ventromedial Prefrontal Cortex - Libedinsky, Camilo; Smith, David V.; Teng, Chieh S.; Namburi, Praneeth; Chen, Vanessa W.; Huettel, Scott A.; Chee, Michael W. (Frontiers in Behavioral Neuroscience, 2011)
Even a single night of total sleep-deprivation (SD) can have dramatic effects on economic decision making. Here we tested the novel hypothesis that SD influences economic decisions by altering the valuation process. Using functional magnetic resonance imaging (fMRI) we identified value signals related to the anticipation and the experience of monetary and social rewards (attractive female faces). We then derived decision value signals that were predictive of each participant’s willingness to exchange money for brief views of attractive faces in an independent market task. Strikingly, SD altered decision value signals in ventromedial prefrontal cortex (VMPFC) in proportion to the corresponding change in economic preferences. These changes in preference were independent of the effects of SD on attention and vigilance. Our results provide novel evidence that signals in VMPFC track the current state of the individual, and thus reflect not static but constructed preferences.